Duplex stainless steel and preparation method thereof

By adjusting the component ratio and process processing of duplex stainless steel, the performance problems caused by the reduction of nickel content are solved, and duplex stainless steel with high mechanical properties and corrosion resistance is prepared to meet the needs of the new energy field and reduce production costs.

CN119265485AInactive Publication Date: 2025-01-07XIANGTAN XINHUA SPECIAL STEEL MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411403221.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing duplex stainless steels increase nickel content to meet the needs of the new energy field, increasing carbon and nitrogen content will reduce their mechanical, processing and corrosion resistance, and the scarcity of nickel leads to increased production costs.

Method used

By adjusting the component ratio in duplex stainless steel, reducing nickel content, increasing the content of manganese, aluminum and silicon, the biphasic structure calculation model is used to optimize the ratio of ferrite and austenite, combined with uniform temperature treatment, hot rolling, solidification By dissolution and aging treatment, duplex stainless steel with good processing properties, mechanical properties and corrosion resistance are prepared.

Benefits of technology

Duplex stainless steel with low nickel content has high tensile strength, yield strength and elongation, which significantly improves its application performance in the new energy field and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075826240000101
    Figure BDA0005075826240000101
Patent Text Reader

Abstract

The invention belongs to the technical field of metal materials, and particularly relates to duplex stainless steel and a preparation method thereof. The duplex stainless steel is prepared from the following components in percentage by mass: 19.8 percent to 21.5 percent of chromium, 3.1 percent to 6.5 percent of manganese, 1.13 percent to 1.28 percent of nickel, 0.38 percent to 0.74 percent of molybdenum, 0.25 percent to 0.35 percent of silicon, 0.27 percent to 0.31 percent of nitrogen, 0.12 percent to 0.35 percent of aluminum, 0.021 percent to 0.038 percent of carbon, 0.02 percent to 0.1 percent of copper, 0.03 percent to 0.069 percent of tungsten, 0.6 ppm to 0.8 ppm of boron and the balance of iron and inevitable impurities. The duplex stainless steel disclosed by the invention has good processability, mechanical property and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of metal materials, and specifically relates to a duplex stainless steel and a preparation method thereof. Background Art

[0002] Duplex stainless steel is a stainless steel that has the characteristics of both austenitic and ferritic stainless steel: duplex stainless steel has higher plasticity and toughness than ferrite, and has excellent intergranular corrosion resistance and welding performance, while retaining the brittleness and high thermal conductivity of ferritic stainless steel; compared with austenitic stainless steel, duplex stainless steel also has significantly improved resistance to intergranular corrosion and chloride stress corrosion.

[0003] The components of duplex stainless steel usually include iron, carbon, chromium, nickel, molybdenum, nitrogen and other elements. Among them, chromium and molybdenum are the main elements for forming ferrite, and nickel, carbon and nitrogen are the main elements for forming austenite. However, the demand for nickel in new energy fields such as stainless steel is growing, and nickel is a scarce metal. It is necessary to reduce the nickel content by increasing the carbon and nitrogen content. However, the increase in carbon content will reduce the mechanical, processing and corrosion resistance properties of stainless steel; and for nitrogen, due to its solubility and other limitations, and excessive nitrogen content will also affect the mechanical, processing and corrosion resistance properties of stainless steel. Summary of the invention

[0004] To solve the above problems, the present application proposes a duplex stainless steel and a preparation method thereof. The duplex stainless steel has a low nickel content and has good processing performance, mechanical properties and corrosion resistance.

[0005] This application is implemented through the following technical solutions:

[0006] In a first aspect, the present application provides a duplex stainless steel, consisting of the following components in mass fractions:

[0007] 19.8% to 21.5% chromium, 3.1% to 6.5% manganese, 1.13% to 1.28% nickel, 0.38% to 0.74% molybdenum, 0.25% to 0.35% silicon, 0.27% to 0.31% nitrogen, 0.12% to 0.35% aluminum, 0.021% to 0.038% carbon, 0.02% to 0.1% copper, 0.03% to 0.069% tungsten, 0.6ppm to 0.8ppm boron, the remainder is iron and unavoidable impurities.

[0008] The duplex stainless steel provided in the present application, manganese, aluminum and silicon can significantly reduce the nickel content in the stainless steel, and the duplex stainless steel in the present application has good processing performance, mechanical properties and corrosion resistance.

[0009] In some possible implementations, the duplex stainless steel has a tensile strength of 910 MPa to 960 MPa, a yield strength of 691 MPa to 725 MPa, and an elongation of 40% to 43%.

[0010] In a second aspect, the present application provides a method for preparing the duplex stainless steel provided in the present application, comprising the following steps:

[0011] The mass fraction of each raw material in the duplex stainless steel is preset, the duplex stainless steel raw material is smelted into an ingot, and the ingot is hot-rolled after being subjected to a temperature equalization treatment to obtain a stainless steel plate;

[0012] The stainless steel plate is subjected to solution treatment and aging treatment to obtain duplex stainless steel.

[0013] The duplex stainless steel prepared by the method provided in the present application has good processing performance, mechanical properties and corrosion resistance.

[0014] In some possible implementations, the step of presetting the mass fraction of each component in the duplex stainless steel includes: setting the ratio of ferrite to austenite in the duplex stainless steel, and adjusting the mass fraction of each element in the duplex stainless steel using a duplex structure calculation model according to the ratio; the duplex structure calculation model is:

[0015] W 铁素体 / W 奥氏体 =(1.48W Cr +3.6W Mo +7.9W Si +4.3W W ) /

[0016] (3.13W Mn +1.1W Ni +21W N +32W Al +28W C +8.4W Cu );

[0017] Among them, W 铁素体 is the area ratio of ferrite in duplex stainless steel; W 奥氏体 W is the area ratio of austenite in duplex stainless steel; Cr , W Mo , W Si , W W , W Mn , W Ni , W N , W Al , W C , W Cu , W B 、M Feis the mass fraction of each element; M is the total mass of duplex stainless steel.

[0018] In some possible implementations, the step of smelting the duplex stainless steel raw material into an ingot includes: adding metal chromium, metal manganese, metal nickel, metal molybdenum, silicon nitride, metal aluminum, wolframite and boron nanowires into molten iron, and then casting to obtain an ingot after LF refining and RH refining.

[0019] In some possible implementations, the temperature of the temperature equalization treatment is 1150° C. to 1200° C., and the temperature equalization time is 1 hour to 1.2 hours.

[0020] In some possible implementations, the hot rolling temperature is 1050° C. to 1090° C., and the final rolling temperature is above 850° C.

[0021] In some possible implementations, the temperature of the solution treatment is 1100° C. to 1200° C., and the time is 1.5 h to 2 h.

[0022] In some possible implementations, the total mass of the duplex stainless steel is greater than 500 t, and the temperature of the solution treatment is 1100° C. to 1150° C.

[0023] In some possible implementations, the total mass of the duplex stainless steel is greater than 500 t, and the temperature of the solution treatment is 1150° C. to 1200° C.

[0024] In some possible implementations, the aging treatment is performed at a temperature of 950° C. to 1000° C. and for a time of 1.5 h to 2 h. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.

[0026] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.

[0027] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0028] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0029] The term "mechanical properties" refers to the yield strength, tensile strength, hot plasticity and toughness of duplex stainless steel.

[0030]

Duplex stainless steel

[0031] In a first aspect, an embodiment of the present application provides a duplex stainless steel, which is composed of the following components by mass fraction:

[0032] 19.8% to 21.5% chromium, 3.1% to 6.5% manganese, 1.13% to 1.28% nickel, 0.38% to 0.74% molybdenum, 0.25% to 0.35% silicon, 0.27% to 0.31% nitrogen, 0.12% to 0.35% aluminum, 0.021% to 0.038% carbon, 0.02% to 0.1% copper, 0.03% to 0.069% tungsten, 0.6ppm to 0.8ppm boron, the remainder is iron and unavoidable impurities.

[0033] The duplex stainless steel of the embodiment of the present application has good processing performance, mechanical properties and corrosion resistance.

[0034] In the embodiment, the mass fraction of chromium is 19.8% to 21.5%, which can be a typical but non-restrictive mass fraction such as 19.8%, 20%, 21.5%, or a range between any two mass fractions. In this mass fraction range, chromium, as one of the elements forming ferrite in duplex stainless steel, affects the proportion of ferrite in duplex stainless steel; and chromium forms a stable and dense Cr2O3 type passivation film on the surface of duplex stainless steel, improving the corrosion resistance of duplex stainless steel. In addition, the solid solution strengthening effect of chromium improves the yield strength of duplex stainless steel.

[0035] In the embodiment, the mass fraction of manganese is 3.1% to 6.5%, which can be 3.1%, 3.8%, 4.5%, 5.6%, 6.5% and other typical but non-limiting mass fractions or a range between any two mass fractions. In this mass fraction range, manganese, as one of the austenite-forming elements in duplex stainless steel, combined with nitrogen and carbon, can reduce the amount of nickel used, thereby reducing production costs.

[0036] In the embodiment, the mass fraction of nickel is 1.13% to 1.28%, which can be a typical but non-limiting mass fraction such as 1.13%, 1.23%, 1.28%, or a range between any two mass fractions. In this mass fraction range, nickel, as a strong austenite forming element, can stabilize the austenite structure and ferrite structure in the duplex stainless steel, and improve the mechanical properties and corrosion resistance of the duplex stainless steel.

[0037] In the embodiment, the mass fraction of molybdenum is 0.38% to 0.74%, which can be a typical but non-restrictive mass fraction such as 0.38%, 0.45%, 0.67%, 0.74%, or a range between any two mass fractions. In this mass fraction range, molybdenum, as one of the ferrite-forming elements, can enhance the strength and hardness of the ferrite phase, thereby improving the mechanical properties of duplex stainless steel. In addition, molybdenum can also improve the pitting and crevice corrosion resistance of duplex stainless steel in chloride environments.

[0038] In the embodiment, the mass fraction of silicon is 0.25% to 0.35%, which can be a typical but non-limiting mass fraction such as 0.25%, 0.3%, 0.35%, or a range between any two mass fractions. In this mass fraction range, silicon, as one of the ferrite forming elements, improves the mechanical properties of duplex stainless steel through its solid solution strengthening effect.

[0039] In the embodiment, the mass fraction of nitrogen is 0.27% to 0.31%, which can be a typical but non-restrictive mass fraction such as 0.27%, 0.29%, 0.31%, or a range between any two mass fractions. In this mass fraction range, nitrogen, as one of the forming elements of austenite, significantly improves the stability of austenite, thereby optimizing the organizational structure of duplex stainless steel; combined with carbon and manganese, it reduces the amount of nickel to a certain extent, thereby reducing the production cost of duplex stainless steel.

[0040] In the embodiment, the mass fraction of aluminum is 0.12% to 0.35%, which can be a typical but non-restrictive mass fraction such as 0.12%, 0.27%, 0.35%, or a range between any two mass fractions. In this mass fraction range, aluminum, as one of the forming elements of austenite, increases the proportion of austenite in duplex stainless steel. In addition, when preparing duplex stainless steel, the addition of aluminum can reduce some metal materials in duplex stainless steel through aluminothermic reaction, increase the temperature of molten steel, and thus improve the yield rate of duplex stainless steel.

[0041] In the embodiment, the mass fraction of carbon is 0.021% to 0.038%, which can be a typical but non-restrictive mass fraction such as 0.021%, 0.03%, 0.038%, or a range between any two mass fractions. In this mass fraction range, carbon, as one of the forming elements of austenite, combines with manganese and nitrogen to reduce the amount of nickel to a certain extent, thereby reducing the production cost of duplex stainless steel. In addition, carbon also affects the relative content and distribution of ferrite and austenite, optimizes the organizational structure of duplex stainless steel, and improves the comprehensive performance of duplex stainless steel.

[0042] In the embodiment, the mass fraction of copper is 0.02% to 0.1%, which can be a typical but non-limiting mass fraction such as 0.02%, 0.06%, 0.1%, or a range between any two mass fractions. In this mass fraction range, copper affects the formation of austenite in duplex stainless steel to a certain extent, improves the mechanical properties and corrosion resistance of duplex stainless steel, and improves the processing performance of duplex stainless steel.

[0043] In the embodiment, the mass fraction of tungsten is 0.03% to 0.069%, which can be a typical but non-restrictive mass fraction such as 0.03%, 0.052%, 0.069%, or a range between any two mass fractions. In this mass fraction range, tungsten can refine the ferrite and austenite grains of duplex stainless steel, thereby optimizing the structure and properties of duplex stainless steel, and further improving the comprehensive mechanical properties of duplex stainless steel.

[0044] In the embodiment, the mass fraction of boron is 0.6ppm to 0.8ppm, which can be a typical but non-limiting mass fraction such as 0.6ppm, 0.7ppm, 0.8ppm, or a range between any two mass fractions. In this mass fraction range, the hardness, strength, corrosion resistance and processing performance of duplex stainless steel are improved.

[0045] In some embodiments, the duplex stainless steel has a tensile strength of 910 MPa to 960 MPa, a yield strength of 691 MPa to 725 MPa, and an elongation of 40% to 43%.

[0046] [A method for preparing duplex stainless steel]

[0047] A second aspect of the embodiment of the present application provides a method for preparing duplex stainless steel provided in the embodiment of the present application, comprising the following steps:

[0048] S1. The mass fraction of each raw material in duplex stainless steel is preset, the duplex stainless steel raw material is smelted into ingots, and the ingots are hot-rolled to obtain stainless steel plates after temperature equalization treatment.

[0049] S2. After solution treatment and aging treatment, the stainless steel plate is converted into duplex stainless steel.

[0050] The duplex stainless steel prepared by the method for preparing the duplex stainless steel in the embodiment of the present application has good processing performance, mechanical properties and corrosion resistance.

[0051] In some embodiments, in the above step S1, the step of presetting the mass fraction of each component in the duplex stainless steel includes: determining the ratio of ferrite to austenite in the duplex stainless steel, and adjusting the mass fraction of each element in the duplex stainless steel using a duplex structure calculation model according to the ratio;

[0052] The calculation model of the two-phase organization is:

[0053] W 铁素体 / W 奥氏体 =(1.48W Cr +3.6W Mo +7.9W Si +4.3W W ) /

[0054] (3.13W Mn +1.1W Ni +21W N +32W Al +28W C +8.4W Cu );

[0055] Among them, W 铁素体 is the area ratio of ferrite in duplex stainless steel; W 奥氏体 W is the area ratio of austenite in duplex stainless steel; Cr , W Mo , W Si , W W , W Mn , W Ni , W N , W Al , W C , W Cu , W B 、M Fe is the mass fraction of each element; M is the total mass of duplex stainless steel.

[0056] The above-mentioned duplex structure calculation model can provide a theoretical reference for the phase ratio of ferrite and austenite in the duplex stainless steel actually produced: the phase ratio of ferrite and austenite in the required duplex stainless steel can be determined first, and the element ratio of the suitable duplex stainless steel can be calculated by the duplex structure calculation model.

[0057] In some embodiments, the dual-phase structure calculation model calculates the theoretical area ratio of ferrite and austenite to be (0.79-1.77):1. In the exemplary embodiment, it can be a typical but non-limiting area ratio such as 0.79:1, 1:1, 1.2:1, 1.6:1, 1.77:1, or a range between any two area ratios.

[0058] In some embodiments, in the above step S2, the step of smelting the duplex stainless steel raw material into an ingot includes: adding metal chromium, metal manganese, metal nickel, metal molybdenum, silicon nitride, metal aluminum, wolframite and boron nanowires to the molten iron, and then casting to obtain an ingot after LF refining and RH refining. In this case, the use of silicon nitride as the raw material of nitrogen and silicon for duplex stainless steel can increase the solubility of nitrogen in molten steel, thereby increasing the nitrogen content in duplex stainless steel; aluminum can reduce tungsten in wolframite and silicon in silicon nitride through aluminothermic reaction, so that tungsten and silicon are in situ reduced to single substances in duplex stainless steel to form ferrite forming elements, and can cooperate with chromium to improve the corrosion resistance of stainless steel. LF refining and RH refining are conventional technologies in the field, and the refining temperature and other conditions can be adjusted according to the actual smelting process, and are not particularly limited in the embodiments of the present application. However, as an example, the temperature of LF refining is 1430℃~1500℃, and the temperature of RH refining is 1380℃~1460℃.

[0059] In some embodiments, the purity of the metal chromium is 99.9% or more, the purity of the metal manganese is 99.9% or more, the purity of the metal nickel is 99.9% or more, the purity of the metal molybdenum is 99.9% or more, the purity of the silicon nitride is 99.9% or more, and the purity of the metal aluminum is 99.9% or more. In this case, the higher purity of the metal raw materials improves the yield and performance of the duplex stainless steel.

[0060] In some embodiments, the mass fraction of tungsten in wolframite is 60% to 70%. In exemplary embodiments, it can be 60%, 68%, 70% or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0061] In some embodiments, the diameter of the boron nanowire is 20 nm to 100 nm. In exemplary embodiments, the diameter may be 20 nm, 50 nm, 100 nm, or other typical but non-limiting diameters, or a range between any two diameters.

[0062] In some embodiments, in the above step S2, the temperature of the temperature equalization treatment is 1150°C to 1200°C. In the exemplary example, it can be a typical but non-limiting temperature such as 1150°C, 1180°C, 1200°C, or a range between any two temperatures. In some embodiments, in the above step S2, the time of the temperature equalization treatment is 1h to 1.2h. In the exemplary example, it can be a typical but non-limiting time such as 1h, 1.1h, 1.2h, or a range between any two times. In this case, the temperature equalization makes the overall temperature of the ingot tend to be consistent, and during the subsequent hot rolling, the microstructure of the stainless steel is uniformly transformed, so that the ferrite and austenite in the stainless steel are evenly distributed.

[0063] In some embodiments, in the above step S2, the rolling temperature of hot rolling is 1050°C to 1090°C, and in the exemplary example, it can be a typical but non-limiting temperature such as 1050°C, 1070°C, 1090°C, or a range between any two temperatures. In some embodiments, in the above step S2, the final rolling temperature is above 850°C, and in the exemplary example, it can be a typical but non-limiting temperature such as 850°C, 900°C, 950°C, or a range between any two temperatures.

[0064] In some embodiments, in the above step S2, the thickness of the stainless steel plate is 9 mm to 12 mm. In an exemplary embodiment, the thickness may be 9 mm, 10 mm, 11 mm, 12 mm, or other typical but non-limiting thicknesses or a range between any two thicknesses.

[0065] In some embodiments, in the above step S3, the temperature of the solution treatment is 1100°C to 1200°C, and in the exemplary embodiment, it can be a typical but non-limiting temperature such as 1100°C, 1150°C, 1200°C, or a range between any two temperatures. In some embodiments, in the above step S3, the time of the solution treatment is 1.5h to 2h, and in the exemplary embodiment, it can be a typical but non-limiting temperature such as 1.5h, 1.8h, 2h, or a range between any two temperatures. In this case, the solution treatment makes the structure and composition of the stainless steel plate more uniform, thereby improving the corrosion resistance and mechanical properties of the duplex stainless steel.

[0066] In some specific embodiments, the total mass of the duplex stainless steel is greater than 500 t, and the temperature of the solution treatment is 1100° C. to 1150° C.

[0067] In some specific embodiments, the total mass of the duplex stainless steel is greater than 500 t, and the temperature of the solution treatment is 1150° C. to 1200° C.

[0068] In some embodiments, in the above step S3, the temperature of the aging treatment is 950°C to 1000°C, and in the exemplary embodiment, it can be a typical but non-limiting temperature such as 950°C, 980°C, 1000°C, or a range between any two temperatures. In some embodiments, in the above step S3, the time of the aging treatment is 1.5h to 2h, and in the exemplary embodiment, it can be a typical but non-limiting time such as 1.5h, 1.8h, 2h, or a range between any two times. In this case, the aging treatment increases the density of the crystal structure in the stainless steel plate, making it denser, reducing internal defects, and thus improving the corrosion resistance of the duplex stainless steel.

[0069] The following is further described in conjunction with specific embodiments.

[0070] Example 1

[0071] Example 1 proposes a duplex stainless steel, which is composed of the following components in mass fractions:

[0072] 20% chromium, 4.5% manganese, 1.23% nickel, 0.45% molybdenum, 0.3% silicon, 0.29% nitrogen, 0.27% aluminum, 0.03% carbon, 0.06% copper, 0.052% tungsten, 0.7 ppm boron, the balance being iron and unavoidable impurities.

[0073] Example 1 also proposes a method for preparing the duplex stainless steel of this embodiment, the steps are as follows:

[0074] (1) The total mass of the prepared duplex stainless steel is set to 600t.

[0075] (2) Adding metallic chromium, metallic manganese, metallic nickel, metallic molybdenum, silicon nitride, metallic aluminum, wolframite and boron nanowires into molten iron, and then casting to obtain an ingot after LF refining and RH refining.

[0076] (3) After the ingot was heated at 1180°C for 1.1 h, it was hot rolled at 1070°C to obtain a stainless steel plate with a thickness of 11 mm. The final rolling temperature during hot rolling was 950°C.

[0077] (4) The stainless steel plate was solution treated at 1180°C for 1.8 h.

[0078] (5) The solution treated stainless steel plate was aged at 980°C for 1.8 h to obtain duplex stainless steel.

[0079] (6) The calculation model of duplex structure of duplex stainless steel is:

[0080] W 铁素体 / W 奥氏体 =(1.48W Cr +3.6W Mo +7.9WSi +4.3W W ) /

[0081] (3.13W Mn +1.1W Ni +21W N +32W Al +28W C +8.4W Cu );

[0082] Among them, W 铁素体 is the area ratio of ferrite in duplex stainless steel; W 奥氏体 W is the area ratio of austenite in duplex stainless steel; Cr , W Mo , W Si , W W , W Mn , W Ni , W N , W Al , W C , W Cu , W B 、M Fe is the mass fraction of each element; M is the total mass of duplex stainless steel.

[0083] The theoretical ratio W of ferrite and austenite is calculated using the above two-phase structure calculation model. 铁素体 / W 奥氏体 It is 1.07:1.

[0084] Example 2

[0085] Example 2 proposes a duplex stainless steel, which is composed of the following components in mass fractions:

[0086] 19.8% chromium, 5.6% manganese, 1.13% nickel, 0.6% molybdenum, 0.28% silicon, 0.31% nitrogen, 0.34% aluminum, 0.038% carbon, 0.03% copper, 0.063% tungsten, 0.6 ppm boron, and the balance is iron and unavoidable impurities.

[0087] Example 2 also proposes a method for preparing duplex stainless steel of this embodiment. The steps are basically the same as those of Example 1, except that the theoretical ratio W of ferrite and austenite is calculated using a duplex structure calculation model. 铁素体 / W 奥氏体 It is 0.91:1.

[0088] Example 3

[0089] Example 3 proposes a duplex stainless steel, which is composed of the following components in mass fractions:

[0090] 21.5% chromium, 4.9% manganese, 1.28% nickel, 0.33% molybdenum, 0.25% silicon, 0.27% nitrogen, 0.15% aluminum, 0.021% carbon, 0.07% copper, 0.03% tungsten, 0.8 ppm boron, the balance being iron and unavoidable impurities.

[0091] Example 3 also proposes a preparation method of duplex stainless steel of this embodiment, the steps are basically the same as those of Example 1, except that: the theoretical ratio W of ferrite and austenite is calculated by using a duplex structure calculation model. 铁素体 / W 奥氏体 It is 1.24:1.

[0092] Example 4

[0093] Example 4 proposes a duplex stainless steel, the composition of which is substantially the same as that of Example 1.

[0094] Example 4 also proposes a method for preparing the duplex stainless steel of this embodiment, and the steps are basically the same as those of Example 1, except that the temperature of the solution treatment in step (4) is 1200°C.

[0095] Comparative Example 1

[0096] Comparative Example 1 proposes an aluminum alloy plate for a battery case, which is composed of the following components in mass fractions: 0.6% manganese, 0.6% magnesium, 0.6% copper, 0.3% silicon, 0.5% iron, 0.01% titanium, 7ppm boron, and the remainder is aluminum and unavoidable impurities.

[0097] Comparative Example 2

[0098] Comparative Example 1 proposes a duplex stainless steel consisting of the following components by mass fraction:

[0099] 20% chromium, 4.5% manganese, 1.23% nickel, 0.45% molybdenum, 0.3% silicon, 0.29% nitrogen, 0.03% carbon, 0.06% copper, 0.052% tungsten, 0.7 ppm boron, the balance being iron and unavoidable impurities.

[0100] Comparative Example 2 also proposes a preparation method of duplex stainless steel of this comparative example, the steps are basically the same as those of Example 1, except that: the theoretical ratio W of ferrite and austenite is calculated using a duplex structure calculation model 铁素体 / W 奥氏体 It is 1.49:1.

[0101] Comparative Example 3

[0102] Comparative Example 3 proposes a duplex stainless steel consisting of the following components by mass fraction:

[0103] 20% chromium, 4.5% manganese, 0.45% molybdenum, 0.3% silicon, 0.29% nitrogen, 0.27% aluminum, 0.03% carbon, 0.06% copper, 0.052% tungsten, 0.7 ppm boron, the balance being iron and unavoidable impurities.

[0104] Comparative Example 3 also proposes a preparation method of duplex stainless steel of this comparative example, the steps are basically the same as those of Example 1, except that: the theoretical ratio W of ferrite and austenite is calculated using a duplex structure calculation model 铁素体 / W 奥氏体 It is 1.12:1.

[0105] Comparative Example 4

[0106] Comparative Example 4 proposes a duplex stainless steel, whose component composition is the same as that of Example 1.

[0107] Comparative Example 4 also proposes a method for preparing duplex stainless steel of this comparative example, and the steps are basically the same as those of Example 1, except that: the solid solution treatment in step (4) is not performed.

[0108] In order to verify the progress of a duplex stainless steel and its preparation method provided in the examples of the present application, the tensile strength, yield strength and elongation of the duplex stainless steel provided in the examples and comparative examples were tested according to GB / T228.1-2010 "Methods for tensile testing of metal materials at room temperature"; the area of ​​ferrite and austenite in the stainless steel was detected by metallographic microscopy and the ratio was calculated. The test results are shown in Table 1 below. The detection steps of the metallographic microscopy method are as follows:

[0109] ① Obtain the stainless steel samples of the embodiments and comparative examples.

[0110] ② Clean the sample and then mechanically polish it.

[0111] ③ Use a metallographic microscope to obtain metallographic micrographs of ferrite and austenite.

[0112] ④ Use Channel 5 image analysis software to calculate the area and ratio of ferrite and austenite in duplex stainless steel.

[0113] Table 1

[0114]

[0115] From Table 1 above, we can at least draw the following conclusions:

[0116] (1) The tensile strength of the duplex stainless steel provided in the embodiment of the present application is above 900 MPa, the yield strength is above 700 MPa, and the elongation reaches 40%, indicating that the duplex stainless steel in the embodiment of the present application has very high mechanical properties.

[0117] (2) In the preparation method of duplex stainless steel provided in the embodiment of the present application, the actual area ratio of ferrite and austenite in the prepared duplex stainless steel is within the range of the area ratio of ferrite and austenite calculated by the duplex structure calculation model, indicating that the duplex structure calculation model proposed in the embodiment of the present application provides a theoretical basis for adjusting the mass fraction of each element in the duplex stainless steel.

[0118] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A duplex stainless steel, characterized in that: It is composed of the following components in mass fractions: 19.8% to 21.5% chromium, 3.1% to 6.5% manganese, 1.13% to 1.28% nickel, 0.38% to 0.74% molybdenum, 0.25% to 0.35% silicon, 0.27% to 0.31% nitrogen, 0.12% to 0.35% aluminum, 0.021% to 0.038% carbon, 0.02% to 0.1% copper, 0.03% to 0.069% tungsten, 0.6ppm to 0.8ppm boron, the remainder is iron and unavoidable impurities.

2. A method for preparing duplex stainless steel as claimed in claim 1, characterized in that: The steps include: The mass fraction of each raw material in the duplex stainless steel is preset, the duplex stainless steel raw material is smelted into an ingot, and the ingot is hot-rolled after being subjected to a temperature equalization treatment to obtain a stainless steel plate; The stainless steel plate is subjected to solution treatment and aging treatment to obtain duplex stainless steel.

3. The method for preparing duplex stainless steel according to claim 2, characterized in that: The step of presetting the mass fraction of each component in the duplex stainless steel comprises: setting the ratio of ferrite to austenite in the duplex stainless steel, and adjusting the mass fraction of each element in the duplex stainless steel using a duplex structure calculation model according to the ratio; the duplex structure calculation model is: IN 铁素体 / IN 奥氏体 =(1.48W Cr +3.6W Mo +7.9W Si +4.3W W ) / (3.13W Mn +1.1W Ni +21W N +32W Al +28W C +8.4W Cu ); Among them, W 铁素体 is the area ratio of ferrite in duplex stainless steel; W 奥氏体 W is the area ratio of austenite in duplex stainless steel; Cr , W Mo , W Si , W W , W Mn , W Ni , W N , W Al , W C , W Cu , W B 、M Fe is the mass fraction of each element; M is the total mass of duplex stainless steel.

4. The method for preparing duplex stainless steel according to claim 2, characterized in that: The steps of smelting the duplex stainless steel raw material into an ingot include: adding metal chromium, metal manganese, metal nickel, metal molybdenum, silicon nitride, metal aluminum, wolframite and boron nanowires into molten iron, and then casting to obtain an ingot after LF refining and RH refining.

5. The method for preparing duplex stainless steel according to claim 2, characterized in that: The temperature of the temperature equalization treatment is 1150° C. to 1200° C., and the temperature equalization time is 1 h to 1.2 h.

6. The method for preparing duplex stainless steel according to claim 2, characterized in that: The hot rolling temperature is 1050°C to 1090°C, and the final rolling temperature is above 850°C.

7. The method for preparing duplex stainless steel according to claim 2, characterized in that: The temperature of the solution treatment is 1100° C. to 1200° C., and the time is 1.5 h to 2 h.

8. The method for preparing duplex stainless steel according to claim 7, characterized in that: The total mass of the duplex stainless steel is more than 500t, and the temperature of the solution treatment is 1100°C to 1150°C.

9. The method for preparing duplex stainless steel according to claim 7, characterized in that: The total mass of the duplex stainless steel is more than 500t, and the temperature of the solution treatment is 1150°C to 1200°C.

10. The method for preparing duplex stainless steel according to claim 2, characterized in that: The temperature of the aging treatment is 950° C. to 1000° C., and the time is 1.5 h to 2 h.

Citation Information

Patent Citations

  • Duplex ferritic austenitic stainless steel

    CN105378135A

  • Super-austenitic stainless steel and optimized design method for alloy components of super-austenitic stainless steel

    CN108396223A

  • Ferrite-based high-strength corrosion-resistant dual-phase alloy and preparation method thereof

    CN113699465A

  • Welded structure and storage tank

    CN114829653A

  • Efficient powder spraying device for cutting stainless steel and high alloy steel

    CN216729994U